Towards a Comparative and International History of School Testing and Accountability - Sherman Dorn; Christian Ydesen (Arizona State University, 2014)
The speed and extent of modern school accountability have obscured the history of testing and accountability. This brief introduction identifies central themes of historical research into educational accountability and recurring traits associated with accountability practices. We hope our colleagues and this special issue will also help to identify future research paths in this field. Some of the central themes found in the historical research on educational accountability contained in this special issue are the connections between accountability and the purposes of schooling in a specific time and place, the relationships between school accountability structures and the state, as well as accountability as a cultural phenomenon. One of the recurring traits found in accountability practices is the role of accountability as a phenomenon that cannot be treated in isolation from society at large along with the attendant questions of power, education access, education management, and social selection. Another key trait is that accountability practices always seem to encompass a certain historically given configuration of stakeholder positions. The research paths pointing beyond the themes treated here are identified as a post-colonial perspective, differences and similarities between public and private sector accountability measures, the "engines" promoting the rise, proliferation and implementation of accountability measures, and finally the exploration of the travelling and movement of accountability ideas, knowledge and practices and how they actually impact and connect with national, regional and local practices.